ACADEMIC BUOYANCY PADA MAHASISWA YANG BEKERJA DAN TIDAK BEKERJA DI JAKARTA - Cristina Hiunata; Linda Linda (Universitas Bunda Mulia, 2018)
ABSTRACT: This research was conducted to test college students’ academic buoyancy, especially working college students and not working college students in Jakarta. Academic bouyancy is the ability of students (in this research is college students) to successfully overcome obstacles and problems that occur in everyday academic life, such as facing tasks and examinations from various subjects intended to measure their abilities (Martin & Marsh in Tarbetsky, Martin & Collie, 2017). Using independent sample of comparative study with quantitative method to understand the differences of academic buoyancy in working college students and not working college students in Jakarta. Data is gathered by using academic buoyancy questionnaire made by researcher based on Martin & Marsh (2010) aspect of academic buoyancy. Academic buoyancy questionnaire validity score range from 0.291 to 0.676 and the reliability score is 0.920. Questionnaire is given to 388 college students in Jakarta. Result shows that there are differences between working college students’ and not working college students’ academic buoyancy in Jakarta. The differences of academic buoyancy is explained by the differences on its aspect, self-efficacy, planning, persistence, and anxiety. Working college students’ and not working college students’ academic buoyancy are both high in categorization, but working college students’ mean are higher than not working college students’ mean. For college students who work can reduce anxiety by setting aside a few minutes every day to calm down and make a priority scale to solve important and urgent things first. For college students who are not working, they are expected to make a learning plan in detail and make a target value that is in accordance with their own abilities.Keywords: academic buoyancy, college student, working, not workingABSTRAK: Penelitian ini dilakukan untuk menguji academic bouyancy pada mahasiswa khususnya mahasiswa yang bekerja dan tidak bekerja di Jakarta. Academic bouyancy adalah kemampuan siswa (dalam penelitian ini adalah mahasiswa) untuk berhasil mengatasi hambatan dan masalah yang terjadi dalam kehidupan akademik sehari-hari, seperti menghadapi tugas-tugas dan ujian dari berbagai mata pelajaran yang dimaksudkan untuk mengukur kemampuan yang dimiliki (Martin & Marsh dalam Tarbetsky, Martin & Collie, 2017). Jenis penelitian yang digunakan adalah penelitian komparatif sampel independen dengan metode kuantitatif untuk mengetahui perbedaan academic buoyancy yang dimiliki oleh mahasiswa bekerja dan tidak bekerja di Jakarta. Pengumpulan data dilakukan dengan menggunakan kuesioner academic buoyancy yang disusun oleh peneliti berdasarkan aspek yang dikemukakan oleh Martin & Marsh (2010). Dari hasil uji coba terhadap kuesioner yang disusun peneliti didapatkan rentang validitas sebesar 0.291-0.676 dan nilai reliabilitas sebesar 0.920. Kuesioner penelitian dibagikan kepada 388 mahasiswa di Jakarta secara secara langsung dan daring. Hasil penelitian menunjukkan bahwa terdapat perbedaan academic buoyancy pada mahasiswa bekerja dan tidak bekerja di Jakarta. Perbedaan juga terlihat pada aspek self-efficacy, planning, persistence, dan anxiety. Academic buoyancy pada mahasiswa bekerja dan tidak bekerja berada pada kategori yang tinggi dengan nilai rata-rata mahasiswa bekerja lebih tinggi daripada nilai rata-rata mahasiswa tidak bekerja. Untuk mahasiswa yang bekerja dapat mengurangi kecemasan yang dirasakan dengan menyisihkan beberapa menit setiap hari untuk menenangkan diri dan membuat skala prioritas untuk menyelesaikan hal yang penting dan mendesak terleboh dahulu. Bagi mahasiswa yang tidak bekerja, diharapkan untuk membuat rencana belajar dengan detil dan membuat target nilai yang sesuai dengan kemampuan diri sendiri.Kata kunci: academic buoyancy, mahasiswa, bekerja, tidak bekerja